Value or Growth Strategy? Empirical Evidence in Brazil - Cordeiro, Rebeca Albuquerque; Machado, Márcio André Veras (Review of Business Management, 2013)
This article aimed at verifying the existence of the value-growth effect and at identifying the variables that best explain their impact on Brazilian stock returns. To this end, we tested book-to-market, profit/price and cash flow/price variables. Two methodological approaches were employed: portfolio analysis, in which portfolios were formed according to each variable of interest; and regression analysis with panel data, based on individual assets. The sample was made up of companies with shares traded in BM&FBovespa during the 1995-2008 period. According to results found, growth stocks presented higher returns than value stocks. Thus, we may conclude that the well-documented value-growth effect is not valid in Brazil, since empirical evidence supported growth strategies. Due to the long research period, results may signal prevalence of growth strategy in the long term. Furthermore, the high volatility of emerging countries’ capital markets was emphasized, as pointed out by Fama and French (1998). Moreover, to establish investment strategies that allow for greater returns, it was found that the variable that best identifies growth stocks is the book-to-market ratio.